PUBLIC PARTICIPATION IN BUDGET OVERSIGHT: A CASE STUDY OF PUBLIC INFORMATION DISCLOSURE IN THE NTT PROVINCIAL GOVERNMENT - Daniel Tonu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study evaluates the dynamics of public participation in budget oversight in East Nusa Tenggara (NTT) Province from 2021 to 2025, focusing on the effectiveness of public information disclosure as an instrument of social control. Through an in-depth analysis of the Public Information Disclosure Index (IKIP) and social audit activities conducted by civil society organizations, this study found a positive correlation between the institutional strengthening of the Information and Documentation Management Officer (PPID) and the intensity of public oversight. Although the NTT Provincial Government successfully achieved the "Informative" predicate with a score of 93.30 in 2025, substantive challenges remain, such as security risks for journalists, low budget literacy, and economic barriers in remote areas. The results show that the availability of budget information (periodic information) has triggered concrete action from civil society groups such as the NTT APPeK Workshop in monitoring infrastructure projects and village funds. However, transforming information into an effective tool of social control requires the institutionalization of more systematic public consultations and stronger legal protection for whistleblowers . This study concludes that administrative transparency in NTT has reached a stage of maturity, but meaningful public participation still requires policy intervention to overcome socio-political barriers on the ground.